Pengembangan video podcast sebagai media pembelajaran geografi pada materi permasalahan dinamika kependudukan di SMA Negeri 1 Tempeh - Farah Nurin Shabrina; Fatiya Rosyida; Ifan Deffinika; Budijanto Budijanto (Universitas Negeri Malang, 2023)
Digital learning media is an example of the integration of science and technology in learning. This research was conducted because it saw the need for learning media that was not optimal in the population dynamics problem material which contains complex population problems and requires media visualization so that students can easily understand the lesson. One of the problems of rampant population dynamics is early marriage, which is done by high school-aged adolescents so that the material for early marriage is representative with high school students. Based on the needs analysis, 97 percent of students considered that early marriage material was more optimally discussed through media in the form of videos equipped with expert speakers in their fields so that the material delivered was valid and trustworthy. This study aims to produce learning media products for population dynamics problems using Video Podcasts. The role of Podcasts in geography can be a medium to discuss trending public issues. The development model used is ADDIE. The product development generated a Video Podcast learning media product equipped by speakers from the Population and Civil Registration Service of Lumajang Regency as experts to discuss the issue of early marriage. Validation tests from both experts revealed that the product was worth testing with minor revisions. The trials were conducted on 30 class XII IPS 3 SMA Negeri 1 Tempeh students. The results of the media trial obtained a score of 77,83 percent which showed that the criteria were very effective and could be used in the geography subject. Researchers are further advised to apply Video Podcast learning media to other sub-materials, except for materials containing formulas and calculations. Media pembelajaran digital merupakan salah satu contoh integrasi IPTEK dalam pembelajaran. Penelitian ini dilakukan karena melihat kebutuhan media pembelajaran yang belum optimal pada materi Permasalahan Dinamika Kependudukan yang memuat permasalahan kependudukan yang kompleks dan membutuhkan visualisasi media agar siswa mudah memahami materi. Salah satu permasalahan dinamika kependudukan yang marak terjadi adalah pernikahan dini, dimana hal ini dilakukan oleh remaja usia SMA sehingga materi pernikahan dini representatif dengan siswa SMA. Berdasarkan analisis kebutuhan, 97 persen siswa menilai bahwa materi pernikahan dini lebih optimal dibahas melalui media berupa video dilengkapi dengan narasumber ahli dalam bidangnya sehingga materi disampaikan valid dan dapat dipercaya. Penelitian ini bertujuan untuk menghasilkan produk media pembelajaran untuk materi Permasalahan Dinamika Kependudukan menggunakan Video Podcast. Peran Podcast dalam geografi dapat menjadi media untuk membahas permasalahan publik yang sedang tren. Model pengembangan yang digunakan adalah ADDIE. Hasil pengembangan berupa produk media pembelajaran Video Podcast yang dilengkapi oleh narasumber dari Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lumajang sebagai ahli untuk membahas permasalahan pernikahan dini. Uji validasi dari kedua ahli mengungkapkan bahwa produk layak untuk diujicobakan dengan revisi kecil. Uji coba dilakukan pada 30 siswa kelas XII IPS 3 SMA Negeri 1 Tempeh. Hasil uji coba media memperoleh skor sebesar 77,83 persen yang menunjukkan kriteria sangat efektif dan dapat digunakan dalam pembelajaran geografi. Peneliti selanjutnya disarankan untuk mengaplikasikan media pembelajaran Video Podcast pada sub materi yang lain, kecuali materi yang mengandung rumus dan perhitungan.